(untitled) (Journal of the Management Sciences, 2025)
This study examined the impact of robotics production techniques on manufacturing industries, focusing on job enhancement, job performance, and wages and benefits. Using a survey of 524 randomly selected participants, data were analyzed with Pearson’s correlation in SPSS. Results revealed a positive and significant relationship between robotics application, job employment, job enhancement, and employee benefits. The study concludes that manufacturing industries should integrate robotics to improve performance and recommends full implementation to support employees in overcoming workplace challenges.